DIGITAL DIVIDE IN THE GENERATION 50+ IN LODZKIE VOIVODESHIP - Wiktorowicz, Justyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The terms “digital divide”, “digital exclusion” refer to the gap between those who have regular access to digital and information technology and are able to effectively use it, and those who do not have such access. The development of ICT infrastructure, with which we are experiencing in recent years, also in the Lodz region, was resulted in smaller digital divide of the first degree (inability to use the appropriate hardware and software), the problem remains, however, the digital divide of the second degree, having their roots in psychological barriers. This applies particularly to the elderly, whose skills are low, and their motivation for skill development is often weak. This paper presents a quantitative assessment of the scale of the digital divide Lodz region residents aged 50 years and older. In the paper I used for this purpose the results of nationwide researches - Social Diagnosis and "Diagnosis of the current situation of women and men aged 50+ on the labour market in Poland", on the basis of which the synthetic index of Internet  versality were constructed. Analysis of these data are done using multivariate statistical analysis. In addition, in the paper the chosen activities undertaken in the fight against digital exclusion in the Lodz region.